Blackberries and their hybrids - Hall, H. K. (Harvey K.); Funt, Richard C. (Crop production science in horticulture, 2017)
This book contains 18 chapters focusing on the growth and development, climatic requirements, fruit quality, chemical composition and health benefits of blackberries and their hybrids. Information on cultivar development and selection, nursery production, vegetative propagation, site selection, preparation, soil management and planting, soil and water management, fertilizer management, pruning and training and plant pathogens, insect pests and weeds and their control are presented. The importance of the proper postharvest storage, transport and marketing of fruits and the economics of blackberry production are also discussed.